Internalisasi Nilai Karakter Pada Kegiatan Orientasi Peserta Didik Baru - Ibrahim Ibrahim; Febri Zulpawinda; Imam Bahari; Febriyanti Febriyanti (Pusat Riset dan Inovasi Nasional, 2023)
This article talks about the internalization of character values ​​in new student orientation activities. In the nutmeg process, there are training activities that are directed so that new students have character values ​​in themselves. Research concentrates in particular through audit writing. rules in directing exploration to achieve research targets. This study uses a literature review, which provides a guide for analyzing the research problem. The results obtained are that character values ​​must exist in new students, one of the activities is through orientation which is carried out when new students enter the school/madrasah. One of the exercises that is expected to frame character values ​​is through student directing exercises. Through these exercises, participants can be encouraged to realize themselves better and develop themselves indicated by the climate and work on all the characteristics and this exercise can prepare them to be free and capable.